Lessons in mortality doctors and patients struggling together - Weisse, Allen B.; ebrary, Inc. (Columbia, Mo. : University of Missouri Press, 2006)
"Writing frankly, Weisse discusses how doctors and patients of cancer, heart disease, stroke, infectious disease, AIDS, and other dire diagnoses deal with illness in the twenty-first century, considering, in turn, how such factors as specialization, rising costs, managed care, the insurance industry, and litigation has changed the practice of medicine"--Provided by publisher.
Introduction -- Lance Armstrong and me -- The crock -- Devotion -- The iron man -- Waste -- Marking time at Hillcrest Home -- The case of the baffling boy : chapter one -- Eddy -- Smart ass -- Victims all -- The end of the road -- Modern medicine -- The survivor -- A man what am -- Other faces of AIDS -- On dying with dignity--and a diagnosis -- The gift -- Time (overdue) for a change -- Stroke -- A letter.
Electronic reproduction.
Keywords: Critically ill -- Psychology; Critically ill -- Conduct of life; Physician and patient; Health behavior; Electronic books